Cololejeunea manilaliana a new synonym of Cololejeunea nilgiriensis (Lejeuneaceae: Marchantiophyta) - Dey, Monalisa; Majumdar, Shuvadeep (Phytotaxa, 2019)
Lejeuneaceae, the largest family of liverworts with over 1800 species in 74 genera, is considered taxonomically very difficult (Ye & Zhu 2018; Zhu & Shu 2018; Zhu et al. 2017; 2018a, b; Zhu et al. 2019; Asthana & Srivastava 2019; Asthana et al. 2019). Cololejeunea (Spruce 1884: 291) Stephani (1891: 208) is the largest genus in the family (He et al. 2012; Zhu et al. 2018b), and represented in India by 63 taxa (Asthana & Srivastava 2003; Asthana & Srivastava 2015; Dey & Singh 2016a,b; Singh & Singh 2016; Manju et al. 2017; Singh 2018; Asthana & Srivastava 2019; Asthana et al. 2019). Among these, one of the recently described species, Cololejeunea manilalia Manju, Chandini & Rajesh (2017: 262) appears to be conspecific with Cololejeunea nilgiriensis Asthana & Srivastava (2003: 27).